Echoes of the Treaties of Madrid (1750) and San Ildefonso (1777) in the readings of the formation of the territory of Argentina and Brazil - Zusman, Perla; Nunes, Sergio (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2019)
The signing of the Treaties of Madrid (1750) and San Ildefonso (1777) between the Spanish and Portuguese Crowns reflects an interest in establishing power without installing potentates in colonial areas under the control of the two Empires. The treaties and the cartography produced by the demarcating parties were adopted by the States of Argentina and Brazil to define their international boundaries and to resolve any conflict arising during the demarcation processes in the late 19th/early 20th century. This article seeks to identify the echoes of these treaties in the literature produced in the social sciences in Argentina and Brazil around the historical geography of the River Plate, with the aim of understanding the conceptions of boundary and territory that underlie these perspectives. Within this framework, we consider that the identification of these visions can help understand, on the one hand, the socio-territorial implications of the signing of the treaties in the formation processes of the National States, and on the other hand, the potentialities and limitations of these studies in analysing the dynamics that took place in the River Plate towards the middle of the 18th century.